3D Metal printed compact high‐Q bandpass filter using folded groove gap waveguide resonator with modified nails - Zhuo‐Wei Miao; Ling Tian (Electronics Letters)
Abstract This paper first presented a novel kind of modified curved nails for building the gap waveguide. By controlling the curved degrees, the realized gap waveguide can achieve a wider electromagnetic band gap range. Subsequently, a groove gap waveguide resonator based on this was proposed that can offer the advantages of miniaturization and high unloaded quality (Qu) values, which is a good candidate for designing low‐loss filters. To further reduce the footprints while maintaining the high Qu, the concept of the folded waveguide was deployed here to construct the so‐called folded groove gap waveguide resonator for the first time. Then, a 4‐pole filter based on the folded groove gap waveguide resonator was designed to validate the possibilities. The designed filter showed comparable performance as its counterparts of half‐mode gap waveguide resonator but with smaller. For rapid prototyping, 3D metal printing was adopted to fabricate the filter concerning its periodical nail structures. The printing quality is acceptable, and the tested results agreed well with the simulated ones.